Group Play as an Instructional Strategy for Enhancing Communication and Social Competence in Deaf Students - Nurjannah, Siti; Rahmatillah, Hilma (Business Finance Analyst Co., 2025)
: Communication competence is an essential ability that children must develop in order to express their thoughts and communicate effectively. Communication serves as a medium for expressing emotions, developing social relationships, and projecting personal identity. However, not all children are able to develop social communication skills independently and at a rapid pace. Some children with special needs require assistance in developing their social communication abilities due to their specific conditions. Deaf students, in particular, often experience communication difficulties, which highlights the need for appropriate strategies to enhance their social communication skills. One strategy that can be applied to improve the social communication abilities of students with special needs is peer-based play. This study employed a qualitative descriptive approach with a case study design aimed at providing an in-depth description of the communication conditions of a student with profound hearing impairment. The findings indicate that students’ communication and social skills improved after the implementation of game-based learning strategies. This study provides empirical support for teachers to implement peer play-based game strategies in instructional practices to support the development of social communication skills among deaf students.